Novel steroid sulfatase inhibitors based on N‐thiophosphorylated 3‐(4‐aminophenyl)‐coumarin‐7‐O‐sulfamates. Issue 6 (13th July 2019) - Daśko, Mateusz; Demkowicz, Sebastian; Biernacki, Karol; Harrous, Amira; Rachon, Janusz; Kozak, Witold; Martyna, Aleksandra; Masłyk, Maciej; Kubiński, Konrad; Boguszewska‐Czubara, Anna
Abstract: In the present work, we described convenient methods for the synthesis of N ‐thiophosphorylated 3‐(4‐aminophenyl)‐coumarin‐7‐ O ‐sulfamates as steroid sulfatase (STS) inhibitors. To design the structures of the potential STS inhibitors, molecular modeling techniques were used. A computational docking method was used to determine the binding modes of the synthesized inhibitors as well as to identify potential interactions between specified functional groups on the inhibitors and the amino acid residues present in the active site of the enzyme. The inhibitory activities of the synthesized compounds were tested in an enzymatic assay with STS isolated from a human placenta. Within the set of newly synthesized compounds, 9e demonstrated the highest inhibitory activity in the enzymatic assay with an IC50 value of 0.201 μM (the IC50 value of 667‐COUMATE in the same test was 0.062 μM). Furthermore, we tried to verify if the obtained STS inhibitors are able to pass through the cellular membrane effectively in cell line experiments. In the course of our study, we determined the STS activity in the MCF‐7 cell line after incubation in the presence of the inhibitors (at 100 nM concentration). For this evaluation, we included newly synthesized compounds 9a‐g and their N ‐phosphorylated analogs 6a‐h, whose synthesis has been previously described. We found that the lowest STS activities were measured in the presence of N ‐phosphorylated derivatives 6e (0.1% of STS activity) and 6f (0.2% of STS activity). The measured STS activity in the presence of 667‐COUMATE (used as a reference) was 0.1%. Moreover, at concentrations up to 1 μM, the most active compounds (6e, 6f, 9b, and 9e ) did not exert any toxic effects on zebrafish embryos.